Tales of Endings and Beginnings: Cycles of Violence as a Leitmotif in the Narrative Structure of the Bhadrakāḷīmāhātmya - Noor van Brussel (Religions, 2020)
The asura’s demise at the hands of the goddess is a theme frequently revisited in Hindu myth. It is the chronicle of a death foretold. So too is the Bhadrakāḷīmāhātmya, a sixteenth century regional purāṇa from Kerala, that narrates the tale of fierce goddess Bhadrakāḷī and her predestined triumph over asura king Dārika. Violence is ubiquitous in this narrative, which was designed with one goal in mind: glorifying the ultimate act of defeating the asura enemy. In its course the story exhibits many kinds of violence: self-harm, cosmic warfare, murder, etc. This paper argues that (1) violence comes to serve as a structural aspect in the text. Reappearing consistently at key moments in the narrative, violence both frames and structures the goddess’s tale. Yet, it is not only the violent act that dominates, it is its accompaniment by equal acts of regeneration that dictates the flow of the narrative, creating a pulsating course of endings and beginnings; (2) these cycles, that strategically occur throughout the narrative, come to serve as a Leitmotif referring to the cyclic tandem of destruction and regeneration that has dominated post-Vedic Hindu myth in many forms. The pulsating dynamic of death and revival thus becomes a specific narrative design that aims to embed the regional goddess within a grander framework of Time.